Composition and Structure of Trees and Saplings in the Catchment Area of PLTA PT. Kerinci Merangin Hydro, Jambi - Fadhlan, Adli; Chairul, Chairul; Solfiyeni; Muchtar, Erizal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
In the management of the catchment area, vegetation plays a crucial role in regulating the hydrological cycle of the ecosystem. However, the construction of dams for hydropower plants and the lack of management of the surrounding area pose a serious threat to forest deforestation. This study aimed to determine the composition and structure of tree stands and tree saplings in the catchment area of PT Kerinci Merangin Hydro Power Plant, Jambi. This method uses a field survey by conducting vegetation analysis on 20 m x 50 m sub-plots with a size of 10 m x 10 m and 5 m x 5 m for trees and saplings. Based on the results, 21 families, 31 genera, 36 species, and 54 individuals were found in the tree strata with Lauraceae as the co-dominant family with a percentage of 12.96%, while the composition of sapling strata plant vegetation found 17 families, 23 genera, 25 species, and 33 individuals with the co-dominant family in the Sapindaceae family with a percentage of 15.15%. Microcos sp. species has the highest INP of 28.80% for tree strata and Dimocarpus sp. for sapling strata at 28.39%. The diversity index was high in the tree stratum at 3.43 and sapling at 3.13. This study can help determine strategies for implementing soil and water conservation, especially forestry regulations, in landscape management.